2013
DOI: 10.1007/s10926-013-9494-1
|View full text |Cite
|
Sign up to set email alerts
|

Communities of Practice to Improve Employment Outcomes: A Needs Assessment

Abstract: HR professionals report a need for current, relevant information on this topic, and participants outline guidelines for developing the CoP and building useful content areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The challenge of accessing and using technology in community mental health practice is consistent with findings from other studies in large systems (Bezyak, Yan, Kang, Burke, & Chan, 2014; Nadeem, Weiss, Olin, Hoagwood, & Horowitz, 2016). This illustrates the need to carefully understand both individual factors such as technical abilities and time constraints as well as organizational factors such as IT capacity and agency policies that can hinder or facilitate the use of technological tools to enhance training and support for programs and practices.…”
Section: Discussionsupporting
confidence: 87%
“…The challenge of accessing and using technology in community mental health practice is consistent with findings from other studies in large systems (Bezyak, Yan, Kang, Burke, & Chan, 2014; Nadeem, Weiss, Olin, Hoagwood, & Horowitz, 2016). This illustrates the need to carefully understand both individual factors such as technical abilities and time constraints as well as organizational factors such as IT capacity and agency policies that can hinder or facilitate the use of technological tools to enhance training and support for programs and practices.…”
Section: Discussionsupporting
confidence: 87%
“…CoPs are being used to support collaboration across national or international jurisdictions for improved knowledge generation and dissemination [ 14 , 18 ], by different types of health practitioners [ 19 , 20 ], and for health policy development to promote, for example, public health financing practices in low-income countries transnationally [ 21 ]. Uncovering the mechanisms that contribute to their success, such as how CoPs interact with formal structures within and across health organizations and how organizations leverage their access to such communities to build their internal knowledge assets, is important for advancing the field [ 16 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having conducted focus groups or interviews with members earlier on in the process might have helped identify these needs and preferences regarding types of activities and use of technology in the RehabMaLL CoP and enabled changes in procedures to improve levels of participation. Bezyak, et al [ 42 ] have shown that conducting focus groups early on in the process can help identify specific needs of members and limits regarding the use of online technology. In particular, their participants noted that even if social media websites such as LinkedIn or Facebook are easy and convenient to use, they are often blocked in the workplace.…”
Section: Discussionmentioning
confidence: 99%